IbM Peternak Sapi Perah dan Pengolahan Susu di Pakem Sleman - Franciscus Asisi Joko Siswanto; Rubiyatno Rubiyatno; Yohanes Dwiatmaka (Universitas Sanata Dharma, 2018)
Community service aims to make (a) the creation of a clean enclosure environment; clean water supply, availability of cattle breeding facilities, availability of standard and hygienic milking equipment, the achievement of milk that meets quality standards, availability of milk heating equipment, and the availability of cooling equipment for milk storage; (b) the creation of marketing networks of milk products, increased ability to use the Internet network for expansion of marketing, increased ability to manage finance through cash book entry and cash out, increasing ability of partner to operate computer-based financial application programs, obtain permission trade mark and entrepreneurship spirit for keeper of dairy cattle. After conducting discussion with Partners 1 and Partner 2, we provided the necessary trainings to help overcome the weaknesses of Partnerss. Partner's weaknesses were limited marketing of milk to cooperatives, cattle raising, simple pasteurization milk processing, business management/marketing, and bookkeeping and profit report creation. There were several steps that were taken, which included: cleaning training, milking training, pasteurized milk making training, business management training, bookkeeping training and production cost calculation, profit and loss calculation, and marketing management training. The results were providing facilities for activities and new markets that can increase revenues.